Answer:
See below
Step-by-step explanation:
It has something to do with the<em> </em><u><em>Weierstrass substitution</em></u>, where we have
![$\int\, f(\sin(x), \cos(x))dx = \int\, \dfrac{2}{1+t^2}f\left(\dfrac{2t}{1+t^2}, \dfrac{1-t^2}{1+t^2} \right)dt$](https://tex.z-dn.net/?f=%24%5Cint%5C%2C%20f%28%5Csin%28x%29%2C%20%5Ccos%28x%29%29dx%20%3D%20%5Cint%5C%2C%20%5Cdfrac%7B2%7D%7B1%2Bt%5E2%7Df%5Cleft%28%5Cdfrac%7B2t%7D%7B1%2Bt%5E2%7D%2C%20%5Cdfrac%7B1-t%5E2%7D%7B1%2Bt%5E2%7D%20%5Cright%29dt%24)
First, consider the double angle formula for tangent:
![\tan(2x)= \dfrac{2\tan(x)}{1-\tan^2(x)}](https://tex.z-dn.net/?f=%5Ctan%282x%29%3D%20%5Cdfrac%7B2%5Ctan%28x%29%7D%7B1-%5Ctan%5E2%28x%29%7D)
Therefore,
![\tan\left(2 \cdot\dfrac{x}{2}\right)= \dfrac{2\tan(x/2)}{1-\tan^2(x/2)} = \tan(x)=\dfrac{2t}{1-t^2}](https://tex.z-dn.net/?f=%5Ctan%5Cleft%282%20%5Ccdot%5Cdfrac%7Bx%7D%7B2%7D%5Cright%29%3D%20%5Cdfrac%7B2%5Ctan%28x%2F2%29%7D%7B1-%5Ctan%5E2%28x%2F2%29%7D%20%3D%20%5Ctan%28x%29%3D%5Cdfrac%7B2t%7D%7B1-t%5E2%7D)
Once the double angle identity for sine is
![\sin(2x)= \dfrac{2\tan(x)}{1+\tan^2(x)}](https://tex.z-dn.net/?f=%5Csin%282x%29%3D%20%5Cdfrac%7B2%5Ctan%28x%29%7D%7B1%2B%5Ctan%5E2%28x%29%7D)
we know
, but sure, we can derive this formula considering the double angle identity
![\sin(x)= 2\sin\left(\dfrac{x}{2}\right)\cos\left(\dfrac{x}{2}\right)](https://tex.z-dn.net/?f=%5Csin%28x%29%3D%202%5Csin%5Cleft%28%5Cdfrac%7Bx%7D%7B2%7D%5Cright%29%5Ccos%5Cleft%28%5Cdfrac%7Bx%7D%7B2%7D%5Cright%29)
Recall
![\sin \arctan t = \dfrac{t}{\sqrt{1 + t^2}} \text{ and } \cos \arctan t = \dfrac{1}{\sqrt{1 + t^2}}](https://tex.z-dn.net/?f=%5Csin%20%5Carctan%20t%20%3D%20%5Cdfrac%7Bt%7D%7B%5Csqrt%7B1%20%2B%20t%5E2%7D%7D%20%5Ctext%7B%20and%20%7D%20%5Ccos%20%5Carctan%20t%20%3D%20%5Cdfrac%7B1%7D%7B%5Csqrt%7B1%20%2B%20t%5E2%7D%7D)
Thus,
Similarly for cosine, consider the double angle identity
Thus,
![\cos(x)= \left(\dfrac{1}{\sqrt{1 + t^2}}\right)^2- \left(\dfrac{t}{\sqrt{1 + t^2}}\right)^2 = \dfrac{1}{t^2+1}-\dfrac{t^2}{t^2+1} =\dfrac{1-t^2}{1+t^2}](https://tex.z-dn.net/?f=%5Ccos%28x%29%3D%20%20%5Cleft%28%5Cdfrac%7B1%7D%7B%5Csqrt%7B1%20%2B%20t%5E2%7D%7D%5Cright%29%5E2-%20%5Cleft%28%5Cdfrac%7Bt%7D%7B%5Csqrt%7B1%20%2B%20t%5E2%7D%7D%5Cright%29%5E2%20%3D%20%5Cdfrac%7B1%7D%7Bt%5E2%2B1%7D-%5Cdfrac%7Bt%5E2%7D%7Bt%5E2%2B1%7D%20%3D%5Cdfrac%7B1-t%5E2%7D%7B1%2Bt%5E2%7D)
Hence, we showed ![\sin(x) \text { and } \cos(x)](https://tex.z-dn.net/?f=%5Csin%28x%29%20%5Ctext%20%7B%20and%20%7D%20%5Ccos%28x%29)
======================================================
![5\cos(x) =12\sin(x) +3, x \in [0, 2\pi ]](https://tex.z-dn.net/?f=5%5Ccos%28x%29%20%3D12%5Csin%28x%29%20%2B3%2C%20x%20%5Cin%20%5B0%2C%202%5Cpi%20%5D)
Solving
![5\,\overbrace{\frac{1-t^2}{1+t^2}}^{\cos(x)} = 12\,\overbrace{\frac{2t}{1+t^2}}^{\sin(x)}+3](https://tex.z-dn.net/?f=5%5C%2C%5Coverbrace%7B%5Cfrac%7B1-t%5E2%7D%7B1%2Bt%5E2%7D%7D%5E%7B%5Ccos%28x%29%7D%20%3D%2012%5C%2C%5Coverbrace%7B%5Cfrac%7B2t%7D%7B1%2Bt%5E2%7D%7D%5E%7B%5Csin%28x%29%7D%2B3)
![\implies \dfrac{5-5t^2}{1+t^2}= \dfrac{24t}{1+t^2}+3 \implies \dfrac{5-5t^2 -24t}{1+t^2}= 3](https://tex.z-dn.net/?f=%5Cimplies%20%5Cdfrac%7B5-5t%5E2%7D%7B1%2Bt%5E2%7D%3D%20%5Cdfrac%7B24t%7D%7B1%2Bt%5E2%7D%2B3%20%5Cimplies%20%20%5Cdfrac%7B5-5t%5E2%20-24t%7D%7B1%2Bt%5E2%7D%3D%203)
![\implies 5-5t^2-24t=3\left(1+t^2\right) \implies -8t^2-24t+2=0](https://tex.z-dn.net/?f=%5Cimplies%205-5t%5E2-24t%3D3%5Cleft%281%2Bt%5E2%5Cright%29%20%5Cimplies%20-8t%5E2-24t%2B2%3D0)
![t = \dfrac{-(-24)\pm \sqrt{(-24)^2-4(-8)\cdot 2}}{2(-8)} = \dfrac{24\pm 8\sqrt{10}}{-16} = \dfrac{3\pm \sqrt{10}}{-2}](https://tex.z-dn.net/?f=t%20%3D%20%5Cdfrac%7B-%28-24%29%5Cpm%20%5Csqrt%7B%28-24%29%5E2-4%28-8%29%5Ccdot%202%7D%7D%7B2%28-8%29%7D%20%3D%20%5Cdfrac%7B24%5Cpm%208%5Csqrt%7B10%7D%7D%7B-16%7D%20%3D%20%20%5Cdfrac%7B3%5Cpm%20%5Csqrt%7B10%7D%7D%7B-2%7D)
![t=-\dfrac{3+\sqrt{10}}{2}\\t=\dfrac{\sqrt{10}-3}{2}](https://tex.z-dn.net/?f=t%3D-%5Cdfrac%7B3%2B%5Csqrt%7B10%7D%7D%7B2%7D%5C%5Ct%3D%5Cdfrac%7B%5Csqrt%7B10%7D-3%7D%7B2%7D)
Just note that
![\tan\left(\dfrac{x}{2}\right) = \dfrac{3\pm 8\sqrt{10}}{-2}](https://tex.z-dn.net/?f=%5Ctan%5Cleft%28%5Cdfrac%7Bx%7D%7B2%7D%5Cright%29%20%3D%20%20%5Cdfrac%7B3%5Cpm%208%5Csqrt%7B10%7D%7D%7B-2%7D)
and
is not defined for ![x=k\pi , k\in\mathbb{Z}](https://tex.z-dn.net/?f=x%3Dk%5Cpi%20%2C%20k%5Cin%5Cmathbb%7BZ%7D)
Answer:
The excluded value is c=0
Step-by-step explanation:
The excluded value is when the denominator goes to zero
(6d^(2)c)/(3c)
3c = 0
c =0
The excluded value is c=0
Answer:
dy/dx = -1/![x^{2}](https://tex.z-dn.net/?f=x%5E%7B2%7D)
Step-by-step explanation:
y = 1/x
dy/dx = d/dx(1/x)
=> dy/dx = d/dx(
)
=> dy/dx = -![x^{-2}](https://tex.z-dn.net/?f=x%5E%7B-2%7D)
=> dy/dx = -1/![x^{2}](https://tex.z-dn.net/?f=x%5E%7B2%7D)
Answer:3
Step-by-step explanation:
Answer:
4
Step-by-step explanation:
pythagoras theorem = a* + b* = c* ( by '*' i mean squared)
2* + b* = square root twenty
4 + b* = 20
b* = 16
b = 4